Pengaruh Smartphone dan Minta Baca terhadap Prestasi Belajar Mahasiswa - Bradley Setiyadi; Sarinah Sarinah (Universitas Indraprasta PGRI Jakarta, 2019)
Reading activities are activities to obtain knowledge or information that should be done for the scientific and educational community. This study aims to determine the extent of student interest in reading by utilizing sophisticated smartphones and aims to further enhance learning achievement. The type of research conducted is descriptive quantitative. The design used is regression between variables. There are two batches used as samples, namely class of 2015 and 2016. The sampling technique is done by random sampling, namely 2015 and 2016. The research instrument used is the distribution of questionnaires and interview documentation given to students of 2015 and 2016. Based on the results of calculations on the model summary obtained by R square is 0.148 or 14.8%, this shows that there is a joint effect between smartphone variables and reading interest on academic achievement of 14.8%, while the rest (100% - 14.8% = 85 , 2%) is influenced by other causes. So it can be concluded that there is an influence of smartphones and reading interest on student achievement in the Educational Administration study program at Jambi University.